ELECTION INFORMATION CAMPAIGN AND THE PERCEPTION OF CAMPAIGN PROPS IN THE BEGINNER ELECTION - Harisman Harisman; Guntur Freddy Prisanto; Niken Febrina Ernungtyas (Universitas Djuanda Bogor, 2021)
The 2019 simultaneous general election formed discourse in society with massive information seeking, rapid information dissemination and discussions related to the general election. Before the election starts, every candidate has the opportunity to campaign. The campaign is an opportunity that is always given to pairs of presidential and legislative candidates. This study aims to describe the search for information about elections by first-time voters and their perceptions regarding campaign props. This study uses a qualitative approach using a case study strategy. The data collection technique used in-depth interviews with four first-time voters who live in Depok, West Java. Based on the results of coding and thematic analysis that has been carried out, there are four main themes that have emerged regarding the search for election information among first-time voters. The four main themes are political engagement, banners as campaign props, social media and information seeking. This study concludes that early voters use social media and campaign props as information source for the election decision.